Google+ for Photographers? January 2013 Update - Brown, Colby (Peachpit Press, 2013)
In June of 2011, Google unveiled its first true foray into the world of social media, Google+. The idea was not to build just another social network but instead to create something much greater-a social fabric connecting the entire Internet. After just 15 months, Google+ is well on its way to achieving its goal, with over 500,000,000 active users engaging with the social features of Google+ and well over 130,000,000 active users on the Google+ network. From the start, it was obvious that Google+ would be a great platform for photographers,āllowing users to interact professionally and personally, while providing an interface that allowed photographers toÅshowcaseÅtheir images in a straightforward, beautiful format.Īn March of 2012, Peachpit released the bookÅ Google+ for Photographers,Å and since then Google+ has continued to evolve and upgrade its network every month. Although the core principles and information found inÅ Google+ for Photographers āre still sound, updates to the platform have prompted the need for an update to coverÅthe changes andḡreat new features, such as Google+ Events and Communities.Īn this short ebook, author Colby Brown covers all of the new Google+ features and enhancements that have launched since March of 2012.ÅWith this ebook, you learn how to: Navigate the new Google+ layout, including Google+ profiles Organize your imagesÅthroughīmprovedÅphoto album features Explore the new optionsāvailableīn Google Hangouts Coordinate Google+ Events and participate in Google+ Communities Navigate the redesigned Google+ mobile app for Android and iOS.